OCTN1 mediates acetylcholine transport in the A549 lung cancer cells: possible pathophysiological implications - Pochini, Lorena; Tedesco, Giusi Elisabetta; Mazza, Tiziano; Scalise, Mariafrancesca; Indiveri, Cesare (Frontiers in Molecular Biosciences, 2024)
A role for acetylcholine in cell proliferation, epithelial mesenchymal transition and invasion has been well assessed and related to the presence of the non-neuronal cholinergic system in lung cancer. For the operation of this non-neuronal system, acetylcholine should be released by a transporter mediated non-quantal process. OCTN1 is one of the transporters able to catalyse acetylcholine efflux in vitro and ex vivo. Using the A549 cell line as a lung cancer model, it has been found that these cells express OCTN1 at a higher level with respect to other cancer cells. The transport capacity of OCTN1 extracted from A549 and reconstituted into proteoliposomes reflects the protein expression profile. The properties of the acetylcholine transport mediated by OCTN1 of A549 in terms of specificity to ligands and ability to catalyse efflux of acetylcholine correspond to those previously described for the same transporter in other cells or to those of the human recombinant protein. OCTN1 is the major player in acetylcholine release in A549 and, therefore, may represent a target for inhibitors able to block the acetylcholine action in this type of aggressive tumors.